PERBANDINGAN MODEL TANAM KONVENSIONAL DAN PLANT FACTORY TERHADAP SAYURAN CAISIM - Amir Hamzah; Risky Alfian; Ninin Khoirunnisa; Wahyu Fikrinda (Universitas Tribhuwana Tunggadewi, 2022)
The aim of this study the first is to know the different effects of treatment with red-blue LED and then compare it to treatment with white fluorescent light for green mustard growth, and the second is for determined the composition from each different treatment to reach the optimum growth of green mustard in the plant factory environment. In this case, treatment with fluorescent light will be used as a control variable for the observation. The research parameter is air temperature, light intensity, and the plant's physical measurements such as diameter and height. This study used a Single Plant Design, the treatment specified in this research was a planting model consisting of the first indoor hydroponic planting model or Plant Factory by applying LED (M1) irradiation, the second outdoor planting model in a greenhouse using full sun irradiation. (M2), and the third cropping model uses direct planting in the field (M3), and the fourth cropping model uses hydroponic planting in open spaces (M4). The result showed that cultivation with the plant factory model produced the best stover wet weight, which was 165.33 g, in contrast to the greenhouse planting model which produced a wet stover weight of 97.33 g and was different from the conventional model, which was 47.33 g. Vegetable wet weight is decent. Consumption also produced the highest with the plant factory planting model, which was 159.67 g per plant, followed by the greenhouse planting model, which was 92.33 g, and different from the conventional model, which was 46.67 g. Whereas if the method converted per ha, the best yields found in the plant factory cultivation model produce caisim vegetables of 27.56 tons/ha, different from the greenhouse planting model is 16.22 tons ha and significantly different from the conventional model which is 7.89 tons/ha.